DOI: 10.14264/uql.2014.385
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the formation of CO2 hydrates in the presence of sodium halides and hydrophobic fumed silica nanoparticles

Abstract: CO 2 capture by trapping the greenhouse gas in clathrates hydrates is proving to be one of the promising options for long term carbon storage. This technology is desirable as it can be deposited in the deep ocean where the suitable pressure and temperature is ready without any extra cost. To date, this method has mostly been of academic interest because the formation of gas hydrates is very slow and requires lots of energy and resources. It is important therefore to develop an efficient and economical process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 215 publications
0
4
0
Order By: Relevance
“…However, gas hydrate nucleation and growth is closely related to the hydrophobicity of gas, and nanoparticles can either be hydrophilic or hydrophobic. Most studies have indicated that hydrophobic nanoparticles in water system facilitate the formation of gas hydrates [25][26][27] , but they inhibit hydrate growth if they locate at the water/oil interface [28] , while other results also showed that nanoparticles facilitate the formation of hydrates at low concentrations [21,23] . However, the researchers did not elucidate the nanoparticle in their experiments is hydrophilic or hydrophobic [21,23] .…”
Section: Introductionmentioning
confidence: 99%
“…However, gas hydrate nucleation and growth is closely related to the hydrophobicity of gas, and nanoparticles can either be hydrophilic or hydrophobic. Most studies have indicated that hydrophobic nanoparticles in water system facilitate the formation of gas hydrates [25][26][27] , but they inhibit hydrate growth if they locate at the water/oil interface [28] , while other results also showed that nanoparticles facilitate the formation of hydrates at low concentrations [21,23] . However, the researchers did not elucidate the nanoparticle in their experiments is hydrophilic or hydrophobic [21,23] .…”
Section: Introductionmentioning
confidence: 99%
“…One serious problem is the low hydrate formation rate, inhibiting the industrial application of the method. Surfactants and hydrotropic E3S Web of Conferences 230, 0100 (2021) Gas Hydrate Technologies: Global Trends, Challenges and Horizons -2020 substances are often used to solve this problem [40], which makes it possible to reveal finer points of the mechanism of the hydrate formation process and its kinetics. However, when adding surfactants, a side effect is often observed that leads to a decrease in the methane hydrate stability.…”
Section: Literature Review and Problem Formulationmentioning
confidence: 99%
“…One of the serious problems is the low rate of hydrate formation, which slows down the industrial application of this method. To solve this problem, surfactants and hydrotropes are often used [18], which makes it possible to find out the fine details of the mechanism of the hydrate formation process and its kinetics. Nevertheless, when adding surfactants, a side effect is often observed, which leads to a decrease in the methane hydrate stability.…”
Section: Literature Data Analysis and Formulation Of The Problemmentioning
confidence: 99%